Research on The Teaching Mode of ASEAN Chinese for Cross-Border E-Commerce Under The Concept of Chinese+: “中文+”理念下东盟“跨境电商汉语”教学模式研究 - Yuan, Li Xiao (Published by Confucius Institute UNS, 2024)
Chinese for E-commerce is an emerging programme of cross-fertilization of language and skills under the concept of ‘Chinese+’. In recent years, some colleges and universities between China and ASEAN countries have carried out cooperation and exchanges on ‘Chinese for Cross-border E-commerce’, which has a huge potential for teaching and learning market demand. Based on the current trend of cooperation, this study finds that the current programme lacks micro teaching design research and has not formed a systematic curriculum system. Therefore, this study follows the principle of ‘practicability’, uses the research method of ‘demand orientation’, and proposes ‘drawing on the experimental teaching method’, ‘constructing Participation, Integration, Creation’ curriculum model, ’Developing a thematic unit teaching programme for e-commerce. ‘The idea suggests to develop a teaching content framework with the theme of e-commerce Chinese language and analyse and sort out its main implementation links. The teaching model fits the real demand of ‘cross-level e-commerce Chinese’ with strong practical applicability, and can provide useful references for micro teaching materials such as syllabus objectives, theme contents and design programmes of the course.